The Speech Act of Thanking in Shakespeare: The Case of Romeo and Juliet and All’s Well that Ends Well - Chahra Beloufa (NOTION: Journal of Linguistics, Literature, and Culture, 2022)
Shakespeare’s written words are not innocent. Many individual words from his dramatic texts can be “obscure or impenetrable”. They are not only meant to embellish the scene and the context, yet their elaboration is aimed to set up meaning and effect. In this part, we will analyze and look at how this utterance operates in characters’ dialogues. We will try to highlight Shakespeare conventionalized thank you, which can be not only a sign of gratitude but a complex emotion that adds to the dramatic situation. In the construction of Shakespeare's dialogues in the plays, many linguistic features are omnipresent and do serve a variety of functions. From a linguistic perspective, thanking is a conversational routine such as advising, requesting and complementing, yet in the use of thanking expressions, there is genuine artistry that Shakespeare wittingly invented. Some words carry risks when negotiating actions. We might think primarily of insults, criticisms and curses. These negative speech acts are not the only damaging and threatening in speech, there is also thanksgiving, which can be regarded as an element bearing risks. The present study focuses on the speech act of thanking in the Shakespearean corpus. The word "thanks" and the formula "I thank you" occurred more than four hundred times in the 37 plays of Shakespeare. Was "thanking" a sincere speech act that acted in the fictional setting of the play? What are the reasons that lead to "thanks" in 16th century Shakespeare? Did Shakespeare succeed to use “thanks” as a successful performative speech act that acts when it is said, or are "thanks" a simple language ornament? To answer these questions, we are going to select specific scenes from Shakespeare's All's Well that Ends Well and Romeo and Juliet examining how the speech act of thanking operates in the plays.